ANALISIS DAMPAK KEBIJAKAN PROGRAM RUJUKAN ONLINE BERJENJANG BPJS TERHADAP PELAYANAN RAWAT JALAN DI POLI PENYAKIT DALAM RSUD DELI SERDANG TAHUN 2019 - Tampubolon, Elmina; Sari, Nur; Hariati, Hariati (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
The era of National Health Security (NHS) enacted tiered referral system start in first level health services, then the hospital type D, type C, type B and type A. Community complaints and a significant decrease in the number of patients in type B hospital especially in outpatient services, the occurrence of patient accumulation and long queues in hospital type C, this indicates that the implementation of this tiered referral system policy program has not run well. The purpose of this study was to look at the impact of the implementation of this tiered referral program policy on outpatient care in poly Internal medicine at the Regional General hospital Deli Serdang Lubuk Pakam. This research is a qualitative research with a prosfective case study approach and uses a fixed case design. This study triangulation to obtain in-depth information on document from SIMRS data, in-depth interviews, Focus Group Discussion (FGD), direct observation in the field without intervention. This reseach was carried out at the Regional General Hospital Deli Serdang Lubuk Pakam , start from January until April 2019. The result of the study show that the implementation of the program has been carried out in accordance with the regulation of Director of Health Service No. 4 of 2014 regarding the referral system for health services carried out in stages. But there were several impacts from the implemention of the program, namely there was a decrease in the number of patient visits, patients cannot get the doctor’s service they want, patients service time is long because the patient must go through several referral procedur first. Recommendation for BPJS as The National Health Insurance Organizing Body to evaluate and improve existing regulations. If it is necessary to make new regulations so that people do not feel like they are being complicated to get services. Recommendation for the hospital to provide better facilities, both facilities and infrastructure, more competent medical personnel and paramedics.